How does centralized isolation treatment strategy affect the medical staff's mental health during the COVID-19 pandemic? - Song, Wei; Huang, Dongmei; Yu, Jiejing (Frontiers in Public Health, 2023)
Background During the coronavirus 2019 (COVID-19) pandemic, the Chinese Government adopted a centralized isolation treatment (CIT) strategy for patients, which has greatly improved the efficiency of the pandemic response. However, compared to those in local hospitals, anti-COVID-19 medical staff in mobile cabin hospitals, where the CIT strategy was adopted, suffered more mental health problems. This study aimed to explore how the CIT strategy affected the medical staff's mental health by comparing anti-COVID-19 medical staff who worked in mobile cabin hospitals to those in fever clinics of local hospitals. Methods Following the standard scale development procedure, this study first developed a scale measuring the mental health of anti-COVID-19 medical staff. Using SPSS 23.0 and Amos 23.0 software, the exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and reliability analysis method were conducted to support the scale development. In the main investigation, a survey method using the developed scale was used, and 839 anti-COVID-19 medical staff from five hospitals in northern China were recruited as participants by snowball-sampling method. The first survey was conducted in February 2020, when the first round of COVID-19 was at a serious time. In April 2020, after the first round of COVID-19 in China was initially contained, and medical staff who worked in mobile cabin hospitals returned to local hospitals, a follow-up survey was conducted on these participants. Using SPSS 23.0 software, a series of 2 × 2 mixed-design ANOVA was conducted, in which working conditions (mobile cabin hospital vs. local hospital) served as a between-subject factor, time points (during vs. after the first round of COVID-19) served as a within-subject variable, and the indicators of the medical staff's mental health served as dependent variables respectively. Results The reliability and validity of the developed scale were desirable. The mental health problems of anti-COVID-19 medical staff were mainly manifested as anxiety, powerlessness, fear of infection, and somatization. Compared to those who worked in local hospitals, anti-COVID-19 medical staff who worked in mobile cabin hospitals where the CIT strategy was adopted suffered more powerlessness, fear of infection, and somatization. After returning to local hospitals, symptoms of fear of infection and powerlessness of medical staff who used to work in mobile cabin hospitals decreased significantly. However, their anxiety symptoms were not relieved, and their somatization symptoms even increased. Conclusion This study implied that the mental health of anti-COVID-19 medical staff in mobile cabin hospitals adopting CIT was worse than in local hospitals. Moreover, with the first outbreak in remission, the mental health recovery of medical staff in CIT hospitals was slower than in local hospitals. Relevant practitioners should pay more attention to the mental health condition of anti-COVID-19 medical staff who work in CIT hospitals. The psychological assistance service for them should continue even after they return to the local hospitals.